Influence of emotional determinants on the portuguese food choices - Guiné, Raquel (2018)
Food choices are a complex system influenced by many factors, such as for example, environmental, political, physiological and emotional. It is well established in the literature that, not only, emotions influence what people choose to eat, but also people’s food choices influence their emotions. Emotional eating is defined as the tendency to eat more in response to negative emotions and can lead to several health problems, namely obesity and eating disorders. Since this is an emergent problem in today’s society, the main goal of this study was to analyse the influence that emotional determinants had on people‘s food choices and also investigate in what extension the particular characteristics of an individual affect the influence that emotional determinants had on people’s food choices. For that purpose, it was created a questionnaire and undertaken a descriptive cross-sectional study on a non-probabilistic sample of 1314 Portuguese participants. To measure the influence that emotional determinants had on the participant’s food choices it was used a scale ranging from -2 to +2, which can be interpreted as follows: [-2.0; -1.5[ - food choices not at all influenced by emotional determinants; [-1.5; -0.5[ - food choices not influenced by emotional determinants; [-0.5; 0.5[ - food choices slightly influenced by emotional determinants; [0.5; 1.5[ - food choices influenced by emotional determinants; [1.5; 2.0] - food choices strongly influenced by emotional determinants. The results revealed that the participants’ food choices were, in general, slightly influenced by emotional determinants (mean scores between -0.5 and 0.5, on scale from -2 to +2). Furthermore, were found significant differences between the groups of all the variables under study (age group, gender, level of education, professional status, area of work or studies, BMI class and the fact that the participants had already experienced an episode of any eating disorder). The participants who already experienced a binge-eating episode were the ones that obtained the highest mean score (0.63 ± 0.79), meaning that in this case, the food choices of those participants were influenced by emotional determinants. Therefore, this study suggests that emotional determinants are influenced by the characteristics of each individual and also that there seems to be a positive association between emotional eating and the existence of eating disorders, especially, binge-eating. Hence, these findings are important to develop and implement strategies that can increase healthier eating habits.